The impact of the economic factor on the process of democratic transition in Iraq after 2003 - Abd, Jabbar Ismail (The International and Political Journal, 2022)
The economic factor plays a major role in the accomplishment of the process of transformation into democracy, as the economy is considered an effective factor in all aspects of life in all countries around the world and it’s the main engine in the success of democracy. The importance of the research stems from highlighting the nature of the relation between the economic factor and the process of democratic transformation in Iraq after 2003, as the main goal is to achieve a democratic state in which citizens have their rights and freedom and the basic guarantees through the ability of the political regime to employ economy in the process of democratic transformation. The research aims to monitor, analyze and clarify the impact of the economic factor in the process of democratic transformation in Iraq after 2003 and to show its most important components and obstacles. One of the most important conclusions reached by the research is that the successive governments to rule Iraq after the changes in Iraq have not succeeded in addressing and combating the scourge of financial and administrative corruption and in finding effective solutions to escape the crises facing the transformation process which negatively affected the ability of the political regime to employ economy in the process of democratic transformation, and this constitutes a group of severe crises that threatened the continuation of the political regime and thus created a crack in the process of building a democratic state.